2017
DOI: 10.1016/j.jad.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of yoga for major depressive disorder

Abstract: This review found some evidence for positive effects beyond placebo and comparable effects compared to evidence-based interventions. However, methodological problems and the unclear risk-benefit ratio preclude definitive recommendations for or against yoga as an adjunct treatment for major depressive disorder. Larger and adequately powered RCTs using non-inferiority designs are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
106
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 55 publications
(126 reference statements)
2
106
0
2
Order By: Relevance
“…14,15 Yoga has been shown to improve psychological and occupational well-being in a variety of populations. [16][17][18] Recent previous studies of yoga programs for frontline professionals have reported improved psychological and occupational well-being, including stress and resilience in university and government employees, 19,20 stress and mood in police officer trainees, 21 self-care, mindfulness, and burnout in nurses, 22 resilience, work engagement, and stress in intensive care unit workers, 23,24 work-related stress in mental health professionals, 25,26 anger and anxiety in active and retired armed forces members, 27 and stress and quality of life in academic medical center employees. 28 Recently, a Kripalu yoga-based program resulted in improvements in stress, depression, mindfulness, and aspects of self-compassion in mental health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Yoga has been shown to improve psychological and occupational well-being in a variety of populations. [16][17][18] Recent previous studies of yoga programs for frontline professionals have reported improved psychological and occupational well-being, including stress and resilience in university and government employees, 19,20 stress and mood in police officer trainees, 21 self-care, mindfulness, and burnout in nurses, 22 resilience, work engagement, and stress in intensive care unit workers, 23,24 work-related stress in mental health professionals, 25,26 anger and anxiety in active and retired armed forces members, 27 and stress and quality of life in academic medical center employees. 28 Recently, a Kripalu yoga-based program resulted in improvements in stress, depression, mindfulness, and aspects of self-compassion in mental health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The core approach of these techniques is an emphasis on focus, mindfulness, and relaxation to enhance overall wellbeing (Goyal et al, 2014;National Center for Complementary and Integrative Health, 2006). While these mind and body practices have been mainly studied in the treatment of chronic pain (Achilefu et al, 2017), depression (Cramer et al, 2017), and stress reduction (Chong et al, 2011) there is growing interest in evaluating how they can be used outside the psychological domain.…”
Section: What Are Complementary and Integrative Health Approaches ?mentioning
confidence: 99%
“…This is not the first report on clinical efficacy of SKY for the treatment of depressive symptoms (3–5); however, it is the first report on its effectiveness in patients who do not respond to antidepressants. The health-related effects and therapeutic potential of SKY were reviewed (6), and yoga-based interventions for mental health are supported by clinical evidence (7).…”
mentioning
confidence: 93%